Microglial fructose metabolism is essential for glioblastoma growth - Leah K. Billingham; Susan L. DeLay; Yasmina Eshac; Tzu-Yi Chia; Shashwat Tripathi; Ian E Olson; Kaylee Zilinger; Jay Subbiah; Zhaoquan Wang; Nishanth S. Sadagopan; Hinda Najem; Guillaume Cognet; et al. (Proceedings of the National Academy of Sciences, 2026)
Glioblastoma (GBM) remains one of the most aggressive and treatment-resistant brain tumors in adults. Its immune microenvironment is dominated by tumor-associated macrophages, including both infiltrating monocytes and brain-resident microglia. While metabolic rewiring of infiltrating myeloid cells has been shown to support tumor progression, the role of microglial metabolism in GBM remains incompletely understood. Here, we demonstrate that microglia uniquely express the fructose transporter GLUT5 and are the only immune cells in the GBM microenvironment capable of metabolizing fructose. Using murine orthotopic glioma and Replication-Competent Avian sarcoma leuko virus Splice acceptor (RCAS)-derived tumor models, we show that global deletion of GLUT5 confers profound resistance to tumor growth. This effect is driven by loss of fructose metabolism in microglia and occurs independently of contributions from peripheral immune compartments. In GLUT5-deficient mice, tumors exhibit increased infiltration and activation of both innate and adaptive immunity, including enhanced antigen presentation, clonal expansion of CD8+ T cells, and increased cytokine production. Depletion of B-cells or CD8+ T cells abrogated survival phenotypes in knockout mice, demonstrating that GLUT5 suppresses adaptive immunity. These findings identify microglial fructose metabolism as a critical regulator of immune suppression in GBM and suggest that targeting this pathway may improve immunotherapeutic responses.